UPAYA MENINGKATKAN KEAKTIFAN BELAJAR PESERTA DIDIK MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM MATA PELAJARAN PENDIDIKAN PANCASILA - Nusro Illahiya; Wahyu Rochmadi, Nur; Mila Amiati, Endah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This Classroom Action Research, utilizing the Kemmis and McTaggart spiral model, aimed to address low student engagement regarding the topic of "Harmony in Diversity" within the *Pancasila* Education subject. The study was conducted over two cycles with 34 students from the Class XI Social Work 1 program at SMKN 2 Malang, integrating the Project-Based Learning (PjBL) model, manual mind mapping, and the Gallery Walk method. Data collected through observation, tests, and documentation were analyzed using both qualitative and quantitative descriptive methods. The results showed that student engagement surged from 26.47% (pre-cycle) to 58.83% (Cycle I), reaching 85.29% in Cycle II. Concurrently, the average class engagement score rose from 52.40 ("less active") to 71.20 ("active") in Cycle I, and further to 83.90 ("highly active") in Cycle II. This improvement was driven by the completion of case-based student worksheets (LKPD), the creation of manual mind maps, and Gallery Walk activities utilizing the "Two Stars and a Wish" strategy. Thus, the combination of PjBL, manual mind mapping, and Gallery Walk proved effective in enhancing student learning engagement.